Self-Enforcing International Agreements and Domestic Policy Credibility - Paola Conconi; Carlo Perroni (Center for Economic Studies and ifo Institute (CESifo), 2003)
We explore the relationship between international policy coordination and domestic policy credibility when both must be self-supporting. Our arguments are presented in the context of a two-country, two-period model of dynamic emission abatement with transboundary pollution, where government policies suffer from a time-consistency problem. In the absence of repeated interaction, any form of coordination - between governments, and between governments and their respective private sectors - improves policy making. Nevertheless, under repeated interaction international policy spillovers can make it possible to overcome the domestic credibility problem; and, conversely, the inability to precommit to policy domestically can help support international policy cooperation.
Keywords: 330; policy commitment; self-enforcing international agreements